TGFβ1 signaling protects chondrocytes against oxidative stress via FOXO1–autophagy axis. Issue 11 (November 2021) - Kurakazu, I.; Akasaki, Y.; Tsushima, H.; Sueishi, T.; Toya, M.; Kuwahara, M.; Uchida, T.; Lotz, M.K.; Nakashima, Y.
Summary: Objective: The forkhead box O1 (FOXO1) transcription factor is a key regulator of autophagy. In chondrocytes, reduced FOXO1 expression with aging causes osteoarthritis due to dysfunction of autophagy, but the mechanisms underlying regulation of FOXO1 expression and the reduction in expression with aging remain unclear. We investigated the mechanism by which transforming growth factor β1 (TGFβ1) signaling regulates the FOXO1–autophagy axis. Methods: Expression of FOXO1 was measured in chondrocytes after TGFβ1 treatment. Immunohistochemistry was performed to estimate the levels of activin receptor-like kinase 5 (ALK5) and FOXO1 in the knee joints of young, middle-aged and old mice. The effects of the ALK5 inhibitor and SMAD3 or SMAD2 knockdown on FOXO1 expression were evaluated. The role of TGFβ1 in autophagy after hydrogen peroxide (H2 O2 ) treatment was analyzed. The protective effect of TGFβ1 against H2 O2 treatment was assessed by cell viability assay and TUNEL assay. Results: TGFβ1 promoted the expression of FOXO1 mRNA and protein. Both ALK5 and FOXO1 expression decreased with aging. ALK5 inhibition and SMAD3 knockdown suppressed induction of FOXO1 expression by TGFβ1, whereas SMAD2 knockdown increased it. TGFβ1 promoted the expression of microtubule-associated proteins 1A/1B light chain 3B (LC3)-I protein via the SMAD3–FOXO1 pathway. Furthermore, under H2 O2 treatment, TGFβ1 promoted expression of LC3-II. TGFβ1 pretreatment suppressed cell death of chondrocytes following H2 O2 treatment, but this protective effect was abolished by FOXO1 knockdown. Conclusions: TGFβ1 protects chondrocytes against oxidative stress via the FOXO1–autophagy axis, and a reduction in ALK5 expression might cause reduced FOXO1 expression with aging.